A molecular signature for CD8+ T cells from visceral leishmaniasis patients. (30th September 2019) - Singh, Bhawana; Bhushan Chauhan, Shashi; Kumar, Rajiv; Singh, Siddharth Sankar; Ng, Susanna; Amante, Fiona; de Labastida Rivera, Fabian; Singh, Om Prakash; Rai, Madhukar; Nylen, Susanne; Sundar, Shyam; Engwerda, Christian
Abstract: CD8 + T‐cell function is compromised in chronic diseases such as visceral leishmaniasis (VL). However, little is known about the changes in gene expression that cause CD8+ T‐cell dysfunction during VL. We used targeted transcriptional profiling of peripheral blood CD8 + T cells from VL patients pre‐ and post‐anti‐parasitic drug treatment, and compared them with the same cell population from healthy endemic controls to assess their activation, differentiation and functional status during disease. We found a predominance of downregulated immune genes in CD8 + T cells from VL patients. However, genes encoding several notable immune checkpoint molecules, including LAG‐3, TIM‐3 and CTLA‐4, cytolytic molecules, such as granzymes A, B and H and perforin, as well as SOCS3, STAT1, JAK2 and JAK3 cytokine signalling genes were found to be increasingly expressed by VL patient CD8 + T cells. Additional studies confirmed increased expression of the inhibitory receptors LAG3 and TIM3 on VL patient CD8 + T cells, thereby identifying these molecules as potential targets to improve antigen‐specific CD8 + T‐cell responses during disease.